Terahertz polarizing component on cyclo-olefin polymer - Ferraro, Antonio; Zografopoulos, Dimitrios C.; Caputo, Roberto; Beccherelli, Romeo (Photonics Letters of Poland, 2017)
Wire-grid polarizers constitute a traditional component for the control of polarization in free-space devices that operate in a broad part of the electromagnetic spectrum. Here, we present an aluminium-based THz wire grid polarizer, fabricated on a sub-wavelength thin flexible and conformal foil of Zeonor polymer having a thickness of 40um. The fabricated device,characterized by means of THz time-domain spectroscopy, exhibitsa high extinction ratio between 30 and 45dB in the 0.3-2.1THz range. The insertion losses oscillate between 0 and 1.1dB andthey stemalmost exclusively from moderate Fabry-Perót reflections and it is engineered forvanishing at 2THz for operation with quantum cascade lasers. Full Text: PDF References I. F. Akyildiz, J. M. Jornet, C. Han, "Terahertz band: Next frontier for wireless communications", Phys. Commun. 12, 16 (2014). CrossRef M.C. Kemp, P.F. Taday, B.E. Cole, J.A. Cluff, A.J. Fitzgerald, W.R. Tribe, "Security applications of terahertz technology", Proc. SPIE 5070, 44 (2003). CrossRef M. Schirmer, M. Fujio, M. Minami, J. Miura, T. Araki, T. Yasui, "Biomedical applications of a real-time terahertz color scanner", Biomed. Opt. Express 1, 354 (2010). CrossRef R.P. Cogdill, R.N. Forcht, Y. Shen, P.F. Taday, J.R. Creekmore, C.A. Anderson, J.K. Drennen, "Comparison of Terahertz Pulse Imaging and Near-Infrared Spectroscopy for Rapid, Non-Destructive Analysis of Tablet Coating Thickness and Uniformity", J. Pharm. Innov. 2, 29 (2007). CrossRef Y.-C. Shen, "Terahertz pulsed spectroscopy and imaging for pharmaceutical applications: A review", Int. J. Pharm. 417, 48(2011). CrossRef A.G. Davies, A.D. Burnett, W. Fan, E.H. Linfield, J.E. Cunningham, "Terahertz spectroscopy of explosives and drugs", Mater. Today 11, 18 (2008). CrossRef J.F. Federici, B. Schulkin, F. Huang, D. Gary, R. Barat, F. Oliveira, D. Zimdars, "THz imaging and sensing for security applications?explosives, weapons and drugs", Semicond. Sci. Technol. 20, S266 (2005). CrossRef D. Saeedkia, Handbook of Terahertz Technology for Imaging, Sensing and Communications (Elsevier, 2013). N. Born, M. Reuter, M. Koch, M. Scheller, "High-Q terahertz bandpass filters based on coherently interfering metasurface reflections", Opt. Lett. 38, 908 (2013). CrossRef A. Ferraro, D.C. Zografopoulos, R. Caputo, R. Beccherelli, "Periodical Elements as Low-Cost Building Blocks for Tunable Terahertz Filters", IEEE Photonics Technol. Lett. 28, 2459 (2016). CrossRef A. Ferraro, D.C. Zografopoulos, R. Caputo, R. Beccherelli, "Broad- and Narrow-Line Terahertz Filtering in Frequency-Selective Surfaces Patterned on Thin Low-Loss Polymer Substrates", IEEE J. Sel. Top. Quantum Electron. 23 (2017). CrossRef B. S.-Y. Ung, B. Weng, R. Shepherd, D. Abbott, C. Fumeaux, "Inkjet printed conductive polymer-based beam-splitters for terahertz applications", Opt. Mater. Express 3, 1242 (2013). CrossRef J.-S. Li, D. Xu, J. Yao, "Compact terahertz wave polarizing beam splitter", Appl. Opt. 49, 4494 (2010). CrossRef K. Altmann, M. Reuter, K. Garbat, M. Koch, R. Dabrowski, I. Dierking, "Polymer stabilized liquid crystal phase shifter for terahertz waves", Opt. Express 21, 12395 (2013). CrossRef D.C. Zografopoulos, R. Beccherelli, "Tunable terahertz fishnet metamaterials based on thin nematic liquid crystal layers for fast switching", Sci. Rep. 5, 13137 (2015). CrossRef G. Isić, B. Vasić, D. C. Zografopoulos, R. Beccherelli, R. Gajić, "Electrically Tunable Critically Coupled Terahertz Metamaterial Absorber Based on Nematic Liquid Crystals", Phys. Rev. Appl. 3, 064007 (2015). CrossRef K. Iwaszczuk, A.C. Strikwerda, K. Fan, X. Zhang, R.D. Averitt, P.U. Jepsen, "Flexible metamaterial absorbers for stealth applications at terahertz frequencies", Opt. Express 20, 635 (2012). CrossRef F. Yan, C. Yu, H. Park, E.P.J. Parrott, E. Pickwell-MacPherson, "Advances in Polarizer Technology for Terahertz Frequency Applications", J. Infrared Millim. Terahertz Waves 34, 489 (2013). CrossRef http://www.tydexoptics.com DirectLink K. Imakita, T. Kamada, M. Fujii, K. Aoki, M. Mizuhata, S. Hayashi, "Terahertz wire grid polarizer fabricated by imprinting porous silicon", Opt. Lett. 38, 5067 (2013). CrossRef A. Isozaki, et al., "Double-layer wire grid polarizer for improving extinction ratio", Solid-State Sens. Actuators Microsyst. Transducers Eurosensors XXVII 2013 Transducers Eurosensors XXVII 17th Int. Conf. On, IEEE, pp. 530?533 (2013). DirectLink A. Ferraro, D. C. Zografopoulos, M. Missori, M. Peccianti, R. Caputo, R. Beccherelli, "Flexible terahertz wire grid polarizer with high extinction ratio and low loss", Opt. Lett. 41, 2009(2016). CrossRef M.S. Vitiello, G. Scalari, B. Williams, P.D. Natale, "Quantum cascade lasers: 20 years of challenges", Opt. Express 23, 5167(2015). CrossRef A. Podzorov, G. Gallot, "Low-loss polymers for terahertz applications", Appl. Opt. 47, 3254(2008). CrossRef